2017
DOI: 10.7324/rjc.2017.1031787
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Performance, Combustion and Emission Characteristics on Biofuel of Novel Pine Oil

Abstract: Increasing fuel prices lead to developing an alternative renewable fuel for internal combustion engines. Pine oil possesses lower viscosity, boiling point and flash point, similar to other plant based fuels like ethanol and eucalyptus oil. Pine oil has been identified to contain terpineol, a higher alcohol, along with pinene, which is an alicyclic hydrocarbon. In this research work, the various performance and emission characteristics of a single cylinder direct injection diesel engine were studied by using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Turpentine can also be added to diesel fuel, but its low cetane number (20 to 25) tends to reduce the engine efficiency [117], although some authors [118] report a 1-2% efficiency improvement when the mixtures are below 40%. It can be used in dual-fuel mode by fumigation, enabling the substitution of up to 75% of the diesel fuel, with noticeable reductions of smoke production [119].…”
Section: Turpentinementioning
confidence: 99%
“…Turpentine can also be added to diesel fuel, but its low cetane number (20 to 25) tends to reduce the engine efficiency [117], although some authors [118] report a 1-2% efficiency improvement when the mixtures are below 40%. It can be used in dual-fuel mode by fumigation, enabling the substitution of up to 75% of the diesel fuel, with noticeable reductions of smoke production [119].…”
Section: Turpentinementioning
confidence: 99%
“…After the experimentation, it was reported that the synthetic oils show the minimum wear scar diameter as compared to the other oil used. Nallusamy et al [142] in this research work studied the various performance and emission characteristics of a single cylinder direct injection diesel engine by using an alternative fuel of the biofuel mixed with pine oil and its blends. The results were compared with standard diesel fuel.…”
Section: Classification Of Nanoparticlesmentioning
confidence: 99%
“…Summary of the tribological studies of lubricating oil with nano-additives[136][137][138][139][140][141][142][143][144][145][146].…”
mentioning
confidence: 99%
“…Previous research proved that biofuels can improve performance and reduce emission in diesel engine 8 . Another research reveals that biofuel made from pine oil can decrease the CO and HC emission in single cylinder diesel engine 9 .…”
Section: Introductionmentioning
confidence: 99%